STUDYING THE GENESIS OF IGNEOUS ROCKS IN ZARIN-KAMAR REGION (SHAHROOD, NORTHEASTERN IRAN) BY RARE EARTH ELEMENTS - Nazemi, Ebrahim; Arian, Mohammad-Ali; Jafarian, Abdolreza; Pourkermani, Mohsen; Yazdi, Abdollah (Gênero & Direito, 2019)
Zarin-Kamar region is located north east of Shahrood (36o37’-36o42’N, 55007’-55012’E). Plutonic rocks in this area belongs to syenite group and their texture is intergranular hypidiomorphic. Volcanic rocks in the area have porphyritic, amygdale intersertal texture. which quartz is also seen among their cavities and porosities. Total concentration of REEs (ΣREE) in the study igneous rocks varies between 450 and 683 ppm. Diagram of Eu/Eu* versus Sr and Eu/Eu* versus Ba show negative anomalies of Eu. This phenomenon as well as Ba and Sr trends show that plagioclase removal has happened during the magma evolution. These rocks have rock has originated from an enriched mantle source. The rate of Dy/Yb in the igneous rocks of the region varies between 1.32 and 2.62. it shows that it stemmed from a garnet lherzolitic source. The rate of (Tb /Yb )N was between 0.97 to 2.25 showing a garnet source. Also other related figures showed that the samples belonged to OIB (Oceanic Island Basalt). The rate of La/Ta was between 6.6 to 14.01. It also showed that they had a source from asthenosphere. The rate of La/Nb was 0.5 to 0.91. It also shows a less crustal contamination among these samples.